PEMBELAJARAN ONLINE TERHADAP PSIKOLOGI MAHASISWA (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2025)
This study aims to examine the impact of online learning on the psychological condition of students at Universitas Nasional Pasim. A descriptive quantitative approach was used, with a questionnaire as the research instrument. The population consisted of 141 second-semester students from various faculties, with a sample of 105 respondents determined using the Slovin formula. The results showed that online learning had a significant effect on students' psychological aspects, with a contribution of 67.3%. Factors such as technological competence, social support, and internal motivation played a role in managing stress and enhancing the effectiveness of online learning. The instrument used was proven to be valid and reliable. These findings are expected to serve as a basis for improving learning systems that support students’ mental health in the digital era.Penelitian ini bertujuan mengetahui dampak pembelajaran online terhadap kondisi psikologis mahasiswa Universitas Nasional Pasim. Pendekatan kuantitatif deskriptif digunakan dengan kuesioner sebagai instrumen. Populasi penelitian berjumlah 141 mahasiswa semester 2 dari berbagai fakultas, dengan sampel 105 orang menggunakan rumus Slovin. Hasil menunjukkan pembelajaran online berpengaruh signifikan terhadap aspek psikologis mahasiswa, dengan kontribusi 67,3%. Faktor seperti kemampuan teknologi, dukungan sosial, dan motivasi internal berperan dalam mengatasi stres dan meningkatkan efektivitas belajar daring. Instrumen telah terbukti valid dan reliabel. Hasil ini diharapkan menjadi dasar perbaikan sistem pembelajaran yang mendukung kesehatan mental mahasiswa di era digital.